OUTCOME OF TRANSCRANIAL REPAIR OF TRAUMATIC CSF RHINORRHEA - Aurangzeb, Ahsan; Ahmed, Ehtisham; Khan, Shahbaz Ali; Ali, Asghar; Ihsan, Adil; Mehmood, Shakir (Journal of Ayub Medical College Abbottabad, 2012)
Background: Traumatic brain injury represents a significant cause of mortality and permanent disability in the adult population. Posttraumatic CSF rhinorrhea is one of the conditions most strongly associated with severe brain injury. Knowledge on the natural history of the illness and the outcomes of patients with transcranial subfrontal approach for posttraumatic CSF rhinorrhea approach may help the neurosurgeon in the decision-making process. This study was conducted to analyse the outcome of trans-cranial sub-frontal approach for traumatic CSF rhinorrhea, with duroplasty and fibrin glue. Methods: This study was carried out in the Department of Neurosurgery, Ayub Medical College, Abbottabad from Jan 2007 to Jun 2011. All patients undergoing trans-cranial sub-frontal repair of traumatic CSF fistulas were included. Where possible primary dural repair was performed under hypotensive general anaesthesia and in the cases where it was not possible, graft was used. This was followed by application of fibrin glue at the repaired site. Graft materials used in this study were taken from fascia lata, pericranium, and temporalis fascia. Results: Out of 27 patients 21 were men and 6 were women. Age of the patients ranged from 17 to 56 (34.5±4.6) years. Main causes of trauma were road traffic accidents (23, 85%), fall from height (3, 11%), and assaults (1, 4%). In 23 (85%) cases no CSF leak was observed in immediate postoperative period as well as during the follow-up visits while in 3 (11%) cases additional lumber punctures were required to augment the repair. One patient failed to respond to surgery and lumbar drainage. Conclusion: The CSF rhinorrhea is commonly seen in patients with anterior skull fractures secondary to head injury. Initially conservative trail should be given to the patients, if it fails then on-lay dural technique followed by fibrin glue application through transcranial approach has good outcome with less chances of complications. Keywords: CSF Rhinorrhea, posttraumatic, repair